Urgensi Keadilan Dalam Penyaluran Zakat di Indonesia - Angga Syahputra; Kaswinata Kaswinata; M. Yasir Nasution; Sugianto Sugianto (Universitas Islam Negeri Alauddin Makassar, 2022)
In the socio-economic context, zakat is one indicator that can answer the needs of people who have a weak economy. According to the BAZNAS report in 2021, the realization of zakat fund collection in Indonesia reached Rp. 14 trillion, or 4.28% of Rp. 327 trillion potential zakat in Indonesia. The discrepancy between the realization and the potential of existing zakat is one of the reasons for the lack of public awareness of tithing through zakat institutions due to a lack of public trust. One of the causes of this emergence is due to injustice in the distribution of zakat. This study will explore the urgency of justice in the distribution of zakat using descriptive qualitative research with the literature study method. This study results that justice in the distribution of zakat by zakat institutions is part of a form of social responsibility, so that this is an absolute thing to strive for and become a target for zakat institutions. Justice in the distribution of zakat will ultimately lead to the attention of the muzakki and become a motivation in paying zakat through institutions. This motivation will ultimately increase the optimization of zakat collection.